Perfil microbiológico de queijo minas frescal industrializado e artesanal comercializado em Goiânia, Goiás - Silva, Lívia Milhomem (2015)
The fresh Minas cheese is widely consumed in Brazil due to its good taste, people's behavior and its easy marketing. It’s a highly sensitive food to microbial contamination due to its characteristics and may have pathogenic microorganisms, a result of a possible failure in the hygienic and sanitary control. The Escherichia coli is a bacterium commonly found in this product and stands out for being indicative of fecal contamination and it’s related to resistance to antimicrobials and high genetic variability between strains found in food. This study evaluated the microbiological quality of fresh Minas cheeses, handmade and industrially produced according to Brazilian legislation. In addition, the aim of this study was also test the susceptibility of E. coli to different antibiotics and identifies its genetic profile. The samples were collected in supermarkets and fairs in the city of Goiânia, Goiás and subjected to microbiological analysis in accordance with the standards established by Resolution RDC nº. 12 of January 2, 2001, of the National Health Surveillance Agency, following the methodology recommended by the American Public Health Association. The antimicrobial susceptibility testing followed the disk diffusion technique in Mueller- Hinton agar and, the genetic variability, was observed by the technique of Pulsed Field Gel Electrophoresis. The analysis detected the presence of coliforms in 100.0% of samples, while fecal coliforms were observed in 10.0% and 14.3% of samples from supermarkets and fairs, respectively. 12.5% of the samples fairs confirmed the presence of Escherichia coli. Handmade cheeses were more contaminated than industrially produced chesses. Of eight isolates, one (8.0%) were sensitive to ampicillin, six (48.0%) showed intermediate susceptibility to cefepime and one (8.0%) was resistant to tetracycline, while 100.0% were sensitive to amoxicillin/clavulanic acid, aztreonam, ceftazidime, ceftriaxone, ciprofloxacin, gentamicin, imipenem, sulfamethoxazole/trimethoprim and piperacillin-azobactam. The cheeses showed high contamination than the limits established to Brazilian legislation, making it unfit for human consumption. These results indicate failures in hygienic sanitary controls in the food chain. The technique of PFGE revealed high genetic variability among isolates while the antibiogram revealed high sensitivity of isolates to antibiotics.